Case report: Muscular tuberculosis with lower-extremity muscular masses as the initial presentation: Clinicopathological analysis of two cases and review of the literature - Zhu, Xiao-wei; Luan, Xing-hua; Jiang, Kai-li; Zhang, Chao; Liu, Shi-hua; Cao, Li; Zhong, Ping; Liu, Zhi-yan (Frontiers in Medicine, 2023)
Background Tuberculosis (TB) is a threat to public health that mostly affects people in developing countries. TB presenting as a soft tissue mass is rare and is usually seen in patients with muscular tuberculosis (MT). Case presentation In this study, we present the clinical, radiographic, and pathological features of two cases and retrospective evaluations of an additional 28 patients who were diagnosed with MT. More patients were men (60.9%) than women (39.1%), with a male-to-female ratio of 1.6:1. The average age among male and female patients was 38.9 and 30.1 years, respectively. MT usually presents with painful or painless muscular nodules on the lower limbs. Imaging findings, including ultrasound, CT, and MRI, can be used to identify lesions and sites for biopsy. The most typical histopathological feature of MT is granulomatous inflammation with caseous necrosis and epithelioid granulomata. Acid-fast bacilli stain and polymerase chain reaction (PCR) assays are helpful in identifying tubercle bacillus. Conclusion We describe two MT cases with lower-extremity muscular masses as the initial presentation. The results suggest that muscle biopsy and pathological analysis remain necessary for diagnosis. Most of the patients could be cured with standard antituberculosis therapy.